Large-scale spatial patterns of small-mammal communities in the Mediterranean region revealed by Barn owl diet - Riegert, Jan; Šindelář, Jiří; Zárybnická, Markéta; Horáček, Ivan (Scientific reports, 2021)
Due to mainly opportunistic hunting behaviour of Barn owl can be its diet composition used for assessing local structure of small-mammal community. We evaluated the structure of small-mammal communities in the Mediterranean region by analysing Barn owl diet using own pellets and literature data (85 localities comprising 182,343 prey individuals). Contrary to widely accepted macroecological theory, we found a latitudinal increase of small-mammal alpha diversity, a less distinct west–east increase and lower diversity on islands. The mean prey weight decreased with increasing latitude, while on islands it decreased with increasing island area. The mean prey weight on islands was further negatively affected by mean land modification by human and positively affected by its range. The diet diversity on islands was not affected either by island area or its distance from the mainland. Its composition largely conformed to the main pattern pronounced over whole the region: an unexpected homogeneity of small-mammal community structure. Despite high beta diversity and large between-sample variation in species composition, Crocidura (+ Suncus etruscus ) and murids ( Apodemus , Mus , Rattus , in marginal regions partly replaced by gerbillids, Meriones or Microtus ) composed more than 90% of owl prey in 92% of samples. Peak abundances of these widespread species are associated with a dynamic mosaic of dense patches of sparse herb vegetation and evergreen sclerophyllous shrublands interspersing areas of human activity, the dominant habitat of the inner Mediterranean and richest food resource for foraging Barn owls. The respective small-mammal species can be looked upon as invasive elements accompanying large scale human colonization of the region since the Neolithic and replacing original island biota. Our study documented that desertification of the Mediterranean played an important role in shaping inverse latitudinal gradient in diversity of small-mammals that contradicts to widely accepted mecroecological theory.